Economic perspectives on key issues - Johnson, Peter (ed.); Thomas, Barry (ed.) (Oxford, 1985)
This book shows the contribution that economics can make to understanding some of the most important issues of today. Issues such as Third World poverty, nuclear deterrence and unemployment are presented as they are in reality not selected and defined to make them amenable to economic analysis. The book is suitable for use on a wide range of introductory courses and is intended to complement a principles text. It also sets the contribution of economics in the context of perspectives from other disciplines: this results in a text which should be of interest to both the introductory student and the general reader.
Keywords: Social sciences